RANGE OF PROBLEMS OF THE SERVICE ORGANIZATION AND POSSIBLE SOLUTIONS FOR THE BORDER CONTROL UNITS - Agafonovs, Eduards; Čerpinska, Aija; Počkajevs, Sergejs (Border Security and Management, 2018)
The authors of this paper describe the current situation in the Border Control Units of the State Border Guard of the Republic of Latvia and, based on the study of regulatory enactments, summarize the service information on the development of the concept of border control in the international law, the essence of its implementation, the principles and mechanisms of the establishment of the infrastructure and engineering equipment that is necessary for the state border control, as well as the role of the border control in the framework of the cooperation.